P417 ASSESSMENT OF RESIDUAL CARDIOVASCULAR RISK AFTER STENTING: THE ROLE OF IMAGING. (18th May 2022) - Micillo, M; Cocco, M; Cossu, A; De Raffele, M; Boccadoro, A; Campo, G; Guardigli, G; Tonet, E
Abstract: Background: Reduction of residual risk after myocardial infarction (MI) represents the main goal in secondary prevention. Imaging may provide additional evidence beyond the monitoring of risk factors. Clinical Case: In June 2019 a 29–year old man, Pakistani ethnicity, former smoker with family history of cardiovascular disease experienced a myocardial infarction without ST–segment elevation. Coronary angiography revealed a severe disease of circumflex branch (LCx) and of second obtuse marginal branch (OM2) treated with drug eluting stent (DES) implantation. A strong medical therapy was planned including dual antiplatelet therapy, high–potency statin and ACE inhibitor. The year after, a new coronary angio was performed because of effort angina: intrastent restenosis of LCx–OM2 was highlighted and treated with balloon, associated with a critical disease of right coronary artery (RCA), treated with DES. In the following months, the patient experienced three hospitalization for unstable angina related to critical intra–stent restenosis of LCx and intermediate stenosis of left anterior descendent (LAD). In order to better understand the subtle mechanism of patient's symptoms, an invasive assessment of microvascular disease was performed, showing microvascular dysfunction (IMR 30; CFR 2.2; RRR 2.7). Additionally, coronary angio images raised the suspicion of positive remodeling on mid tract of RCA and LCx, expression of a progressive and high risk atherosclerosis (Figure 1 ). A close follow up was planned: a coronary computed tomography angiography (CCTA) 4 months after the last angio was performed aiming the assessment of atherosclerosis progression. CT images showed patency of the previously placed stents. A severe amount of positive plaque remodeling of RCA and LCx was documented: it was characterized by hypodense eccentric plaque (<30 HU) with some little calcific spot near to the lipid core. These features underlined the presence of high–risk coronary plaque (Figure 2, Figure 3 ). Taking into account clinical history, instrumental and laboratory data, the patient was a candidate for therapy with PCSK9 inhibitors, which previously demonstrated an effect on reduction of plaque's lipid core. Conclusions: CT coronary represents an excellent method for the assessment of residual risk in ischemic patients thanks to its ability to detect not only stenotic plaques, but also high–risk features of atherosclerosis, thus allowing therapeutic optimization.